Reading to writing: effects of authentic readings on novice Spanish students’ writing / Ana I. Capanegra - I. Capanegra, Ana (Universiti Teknologi MARA, Kedah, 2014)
The current study examined the effects of authentic readings on the written production of college-level novice Spanish students, especially on content/vocabulary and text organization. The experimental and control groups had six written assignments over a 4-month period, which included a pretest and posttest to measure overall writing abilities of the participating groups. The experimental group was asked to read four different authentic texts before writing, whereas the control group completed the writing assignments without the prior reading activity. The gains of the combined dependent variables content/vocabulary and text organization were analyzed. The results of an ANOVA performed on the participants’ gains in overall writing scores from pretest (Writing Assignment 1) to posttest (Writing Assignment 6) showed that authentic reading comprehension activities did not improve their writing abilities. The results of a MANOVA performed on the gains from Writing Assignment 2 to Writing Assignment 5 in terms of content/vocabulary and text organization showed no main effect for group or gender but did reveal an interaction. The reading assignment enhanced females’ content/vocabulary and text organization while undercutting males’ progress. Finally, the findings of the post experimental survey administered to the participants in the experimental group revealed moderately positive attitudes toward the use of authentic readings prior to the writing assignments. The gender differences revealed by this investigation warrant further and more detailed research to determine possible underlying causes.